PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN ISLAM BERBASIS KETERAMPILAN KOMUNIKASI DALAM MENINGKATKAN KOMPETENSI PESERTA DIDIK - Sri Wahyuni; Ananda Solikhatunnisa; Nadia Ismawati; Nur Jamilah Sari; Paija Misladina Hasibuan; Viona Putri Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is based on the problem of low communication skills among students in Islamic education learning which is still dominated by a teacher-centered approach. This condition causes students to be passive and unable to optimally develop their critical thinking skills and social interaction. The purpose of this study is to examine the development of a communication skill-based learning model to improve student competence. This research uses a qualitative approach with a library research method by reviewing various relevant sources, such as academic books, journals, and previous studies. The results show that the implementation of a communication-based learning model is able to improve students’ competencies comprehensively, including cognitive, affective, and psychomotor domains. This model encourages the creation of interactive, participatory, and student-centered learning processes through activities such as discussions, collaboration, and the use of technology. In addition, this model contributes to building students’ self-confidence, enhancing critical thinking skills, and developing social attitudes in accordance with Islamic values. Therefore, a communication skill-based learning model can be used as a strategic alternative to improve the quality of Islamic Religious Education learning in the modern era.